2005
DOI: 10.1590/s0034-89102005000500016
|View full text |Cite
|
Sign up to set email alerts
|

Health, sleep and lack of time: relations to domestic and paid work in nurses

Abstract: ObjectiveTo assess whether reported morbidity and complaints of lack of time and sleep are associated with the burden of professional work and housework among nurses. Methods A cross-sectional exploratory study was carried out among female nurses and nurse assistants (N=206) of a public hospital in Rio de Janeiro, Brazil. Data were collected by means of a questionnaire. The prevalence ratio and 95% confidence intervals were estimated. Results Mean duration of professional work and housework time was 40.4 and 3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
35
0
8

Year Published

2008
2008
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 47 publications
(48 citation statements)
references
References 17 publications
3
35
0
8
Order By: Relevance
“…Concerning this aspect Kranz et al (2005) referred to a higher risk of health symptoms among females devoting more time to both paid and household work. Data on females from a similar population showed that those with long professional work hours were more likely to complain about the lack of time for leisure and rest than those working fewer hours (Portela et al, 2005). Other factors that can mediate the difficulties faced by females is related to the need for recovery from work-induced fatigue as it depend on the recovery time, which may differ between males and females due to different family roles (Jansen et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Concerning this aspect Kranz et al (2005) referred to a higher risk of health symptoms among females devoting more time to both paid and household work. Data on females from a similar population showed that those with long professional work hours were more likely to complain about the lack of time for leisure and rest than those working fewer hours (Portela et al, 2005). Other factors that can mediate the difficulties faced by females is related to the need for recovery from work-induced fatigue as it depend on the recovery time, which may differ between males and females due to different family roles (Jansen et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the imbalance in gender work is a fundamental issue to be considered when analyzing the relationships between gender and work and health (Artazcoz et al, 2001). Some authors emphasize that health outcomes may be mutually influenced by professional and domestic work (Lindfords et al, 2006;Portela et al, 2005;Krantz and Ostergren, 2001). Paid and unpaid work in the home and social support are important elements in the social production of health and illness, though their combined effects on both women and men.…”
Section: Introductionmentioning
confidence: 99%
“…The long working hours have a negative effect both on professional life and also on the social and family life of the individuals affected (1,3) . Difficulties in social relationships and personal activities (1,3) , as also the lack of time for leisure pursuits and health care, are often mentioned as being related to long working hours (1,(3)(4) .…”
Section: Introductionmentioning
confidence: 99%
“…The long working hours have a negative effect both on professional life and also on the social and family life of the individuals affected (1,3) . Difficulties in social relationships and personal activities (1,3) , as also the lack of time for leisure pursuits and health care, are often mentioned as being related to long working hours (1,(3)(4) . Thus, long working hours have been associated to several illnesses and symptoms, including bouts of depression, high blood pressure, muscular and skeletal problems, gastrointestinal disorders, stress and fatigue (4)(5) , and have also been linked to behaviour patterns that are inappropriate for good health, such as a greater consumption of alcohol, cigarette smoking, reduction in the quantity of physical exercise, and an inadequate standard of sleep or other sleep disorders (5)(6) .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation